DYNAMIC SHOT UNTUK MEMPERKUAT REALITAS PADA SINEMATOGRAFI FILM MOCKUMENTARY “BOOKING OUT” - Khanif Irkham Muzaki; Arif Eko Suprihono; Latief Rakhman Hakim (Sense: Journal of Film and Television Studies, 2020)
ABSTRACTThe final project of art creation entitled "Dynamic Shot to Strengthen Reality in The Cinematography of Mockumentary film production “Booking Out” is taking form in a mockumentary film that raises the issue of sexuality in Indonesian society, especially at the city of Yogyakarta.  The film tells the story of a fake online sex worker who wants to gain profit by tricking a man on the internet whose think that he is a sexual worker and paying him money, but in the end he's being caught by the police because of fraud, exploitation, misuse of data along with his sister-in-law's report to the police. Mockumentary film is a work of fictional film which has a visual structure resembling a documentary film and must be able to build its own reality.  Cinematography is one of the fragment of how filmmaker could tell a narrative through visuals and it consists of three aspects, namely camera film, framing and image duration, and that should be one of the main concerns in the creation of a mockumentary film.  The use of dynamic shot as a cinematographic concept in the creation of a mockumentary film "Booking Out" can maximize the exploration of motion on the camera through the use of long take, handheld, and zoom techniques, this is useful as an enhancer of the reality especially in the visual look and mood or atmosphere of the mockumentary film. Keyword : Cinematography, Dynamic Shot, Reality, Mockumentary Film  ABSTRAK            Karya tugas akhir penciptaan seni berjudul Dynamic Shot Untuk Memperkuat Realitas Pada Sinematografi Film Mockumentary “Booking Out” merupakan sebuah karya film mockumentary yang mengangkat isu seksualitas di masyarakat Indonesia, khususnya kota Yogyakarta. Film Mockumentary “Booking Out” bercerita mengenai seorang pekerja seks online palsu, menginginkan keuntungan banyak dari pekerjaannya, namun justru tertangkap polisi karena kasus penipuan, eksploitasi, dan penyalahgunaan data dengan pelapor adik iparnya sendiri.Film mockumentary merupakan sebuah karya film fiksi yang  memiliki struktur visual menyerupai film dokumenter haruslah dapat membangun sebuah realitas kehidupan yang nyata. Sinematografi sebagai salah satu bagian dari cara bertutur sebuah film melalui visual terdiri dari tiga aspek yaitu kamera dan film, framing serta durasi gambar, patutlah menjadi salah satu perhatian utama dalam penciptaan sebuah film mockumentary. Penggunaan dynamic shot sebagai konsep sinematografi pada penciptaan film mockumentary “Booking Out”  dapat memaksimalkan eksplorasi gerak pada kamera melalui penggunaan teknik longtake, handheld, dan juga zoom, hal ini berguna sebagai pemerkuat realitas look (nuansa) dan mood (suasana) sebuah film mockumentary. Kata Kunci : Sinematografi, Dynamic Shot, Realitas, Film Mockumentary